An Analysis of Flood Forecasting Parameters in the Bandar Segamat Sub-Basin using HEC-HMS - Azli, Nur Ellissa Anis (Progress in Engineering Application and Technology, 2025)
Bandar Segamat frequently experiences significant flooding due to heavy monsoon rainfall that leads to rapid runoff and river overflow (Bernama, 2023). From the heavy rain, it created a small island at the Bandar Segamat. The Sungai Segamat Sub-basin, like many other river basins, faces challenges such as water scarcity, floods, and environmental degradation, necessitating effective hydrological modelling techniques to address these issues. This study uses Hydraulic Modelling System (HEC-HMS) to simulate the hydrologic processes of the Segamat River Basin by optimizing 3 main parameters for flood forecasting which are loss, transform and baseflow to improve model accuracy and ensure the most accurate result is achieved. This study also measures the Nash-Sutcliffe Efficiency (NSE) value which is a widely used indicator in hydrological modeling in order to evaluates a model's performance in comparison to observed data. This study  This research uses accessible data and softwares to perform a qualified NSE value and also R2 for calibration and validation. Results shows that increament in land use and lag time plays important role for flood forecasting with the NSE value is 0.732 and the R2 is 0.75. Comparing the result with previous study, it showed that this current study had increased the result of NSE and R2 due to the improvement of the three parameters. The enhanced data shows that it is more suitable for urban areas and long-duration rainfall events. The study concludes that incorporating updated land use data and refining lag time analysis significantly improve hydrologic modeling for flood forecasting in urban settings. It is recommended to integrate real-time data assimilation and explore advanced techniques such as machine learning to further refine predictive accuracy and enhance flood mitigation strategies.